New Amphiphilic Squalene Derivative Improves Metabolism of Adipocytes Differentiated From Diabetic Adipose-Derived Stem Cells and Prevents Excessive Lipogenesis - Ganbold, Munkhzul; Ferdousi, Farhana; Arimura, Takashi; Tominaga, Kenichi; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2020)
Squalene (Sq) is a natural compound, found in various plant oils, algae, and larger quantity in deep-sea shark liver. It is also known as an intermediate of cholesterol synthesis in plants and animals including humans. Although evidences demonstrated its antioxidant, anticancer, hypolipidemic, and hepato- and cardioprotective effects, its biological effects in cellular function might have been underestimated because of the water-insoluble property. To overcome this hydrophobicity, we synthesized new amphiphilic Sq derivative (HH-Sq). On the other hand, adipose-derived stem cells (ADSCs) are a valuable source in regenerative medicine for its ease of accessibility and multilineage differentiation potential. Nevertheless, impaired cellular functions of ADSCs derived from diabetic donor have still been debated controversially. In this study, we explored the effect of the HH-Sq in comparison to Sq on the adipocyte differentiation of ADSCs obtained from type 2 diabetic subject. Gene expression profile by microarray analysis at 14-day of adipogenic differentiation revealed that HH-Sq induced more genes involved in intracellular signaling processes while Sq activated more transmembrane receptor pathway related genes. In addition, more important number of down- and up-regulated genes by Sq and HH-Sq were not overlapped, suggesting the compounds might not only have difference in their chemical property but also potentially exert different biological effects. Both Sq and HH-Sq improved metabolism of adipocytes by enhancing genes associated with energy homeostasis and insulin sensitivity, SIRT1, PRKAA2, and IRS1. Interestingly, Sq increased significantly early adipogenic markers and lipogenic gene expression such as PPARG, SREBF1, and CEBPA; but not HH-Sq in dose-dependent manner. As a consequence, smaller and fewer lipid droplet formation was observed in HH-Sq-treated adipocytes. Based on our findings, we report that both Sq and HH-Sq improved adipocyte metabolism; but only HH-Sq prevented excessive lipogenesis without abrogating adipocyte differentiation. The beneficial effect of HH-Sq provides an importance of synthesized derivatives from a natural compound with therapeutic potentials in the application of cell therapies.